Causas de la ansiedad en adolescentes durante la pandemia por Covid-19: Una revisión sistemática - Moscoso Roqu, Fiorella (2024)
During the year 2020, the Covid-19 pandemic began, which seriously impacted adolescents, forcing them to stop certain daily activities such as their studies and socialization, causing deterioration in their mental health and affecting their development in various areas. For this reason, a theoretical, systematic review study was carried out that considered various published studies regarding anxiety during Covid-19 in adolescents. Thirty articles were located, of which six were excluded. The results allowed us to establish that, during the Covid-19 pandemic, negative effects were evident on the mental health of adolescents, so that the most frequent percentages of anxiety levels during Covid-19 were in the moderate and high categories.